2009
DOI: 10.1016/j.immuni.2009.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Differential Recognition of CD1d-α-Galactosyl Ceramide by the Vβ8.2 and Vβ7 Semi-invariant NKT T Cell Receptors

Abstract: CD1d presents lipid-based antigens (Ag) that are recognised by the semi-invariant T cell receptor (TCR) expressed on Natural Killer T (NKT) cells. While the TCR α-chain is typically invariant, the TCR β-chain expression is more diverse, particularly in mice where at least three different Vβ chains are commonly expressed. We report the structures of Vα14-Vβ8.2 and Vα14-Vβ7 NKT TCRs in complex with CD1d-α-galactosylceramide (α-GalCer), as well as a 2.5 Å structure of the human NKT TCR-CD1d-α-GalCer complex. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

27
355
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 198 publications
(385 citation statements)
references
References 45 publications
(80 reference statements)
27
355
3
Order By: Relevance
“…3B). Consistent with the idea that other CDR2β region residues in the Vβ2 and Vβ7 type I NKT TCRs (11,13) can also bind to CD1d, these tyrosine residues are not present in the Vβ3.1 TCRs of the type II NKT cells. It is noteworthy that all Vβ8.1 and Vβ3.1 TCRs of type II NKT cells carry a negatively charged residue at position 53 in the CDR2β region, whereas a neutral glycine residue is present in most TCRs of type I NKT cells (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…3B). Consistent with the idea that other CDR2β region residues in the Vβ2 and Vβ7 type I NKT TCRs (11,13) can also bind to CD1d, these tyrosine residues are not present in the Vβ3.1 TCRs of the type II NKT cells. It is noteworthy that all Vβ8.1 and Vβ3.1 TCRs of type II NKT cells carry a negatively charged residue at position 53 in the CDR2β region, whereas a neutral glycine residue is present in most TCRs of type I NKT cells (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Recent structural studies have suggested the involvement of crucial residues within the CDR2β, CDR1α, and CDR3α loops of the semi-invariant TCR in recognition of the αGalCer/CD1d complex (9)(10)(11)(12). It is notable that two conserved residues (48Y and 50Y) in the CDR2β loop of the type I NKT TCR that contact the CD1d molecule (9)(10)(11)(12) are also present in the Vβ8.1 TCRs of type II NKT cells (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations